The impact of teacher's involvement on decision making for school improvement: a study among teachers' and school leaders in selected private schools in Dubai - MAWAJDEH, ENAS (2021)
The research aims to study the impact of teachers' involvement in decision making, its importance to school effectiveness, job satisfaction, and teachers' stability. Therefore, the literature provides beneficial initiatal information about the decision-making procedure and how it enhances job satisfaction and stability for teachers. This research uses qualitative and quantitative methods to deduce the final conclusions by descriptively analyzing the data received from the mixed-method approach, which gives a complete view of the issues directly related to teacher involvement. The study population includes 150 teachers and 11 school leaders from one of the Dubai schools that has two branches. The research data analysis shows clear evidence that teacher input has a positive impact on school achievement. Teachers are among the most important features that impact the quality of education in school progress. The research asserts that the teachers' involvement affects school performance positively, and the results indicate that involving teachers in school decision-making processes positively impacts school performance. Consequently, leaders should exchange, consult, and share concepts with teachers to improve the school outcomes. Additionally, teachers have the ability and freedom to control their work in the academic parts more than administrative and they are involved in decisions that affect their activities. Furthermore, teachers are satisfied and committed to the current school. Therefore, involving teachers in school decisions, especially decisions related to assessment, teaching methods, and instructional resources, is recommended for school improvement, job satisfaction, and teachers' stability.